2015
DOI: 10.1186/s13014-015-0560-z
|View full text |Cite
|
Sign up to set email alerts
|

Definitive radiotherapy alone over 60 Gy for patients unfit for combined treatment to stage II-III non-small cell lung cancer: retrospective analysis

Abstract: BackgroundElderly patients with non-small cell lung cancer (NSCLC) are frequently treated with radiation therapy (RT) alone, due to poor performance status or underlying disease. We investigated the effectiveness of RT over 60 Gy administered alone to NSCLC patients who were unfit or rejecting for combination treatment.Methods and materialsFrom April 2002 to July 2010, 83 patients with stage II-III NSCLC, aged over 60 years, treated by RT alone with a curative aim were analyzed. Radiation was targeted to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The proportion of patients receiving cCHRT (33%) was comparable to other elderly-specific studies (33-41%) [14,22] and less often administered to patients aged P75 with PS P 2 and severe comorbidity. Both PS and comorbidity are important indications for treatment toxicity and survival as reflected by the most common motives for omitting cCHRT and should be analyzed carefully before treatment decision-making [5,7,9,21]. Not choosing intensive treatment could originate from cherishing a good QoL instead of longer survival time at the end of life [7,11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proportion of patients receiving cCHRT (33%) was comparable to other elderly-specific studies (33-41%) [14,22] and less often administered to patients aged P75 with PS P 2 and severe comorbidity. Both PS and comorbidity are important indications for treatment toxicity and survival as reflected by the most common motives for omitting cCHRT and should be analyzed carefully before treatment decision-making [5,7,9,21]. Not choosing intensive treatment could originate from cherishing a good QoL instead of longer survival time at the end of life [7,11].…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, worse survival for cCHRT could also be explained by poor-risk patients receiving carboplatin more often and higher survival rates can be reached in selected patients receiving cisplatin [39]. Due to minor differences in survival and less adverse events, it can be suggested that sCHRT is more feasible than cCHRT in unselected elderly [4] and RT remains an alternative for CHRT in patients with severe comorbidity [9,10]. However, cCHRT should not be denied to selected elderly patients [14,19,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly, SR has not been reported previously in the ALK rearranged subpopulation. Local recurrence-free survival rate at 2 years following radical radiotherapy alone is offered at approximately 29% with modern treatment in the unselected NSCLC population [54], but this value is thought to be lower in oncogenic NSCLC [5,7]. Local control was achieved for 24 months in the case outlined despite ALK rearrangement (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For inoperable stage II patients, the optimal treatment is much less certain. Chemoradiation or radical doses of radiotherapy alone remain a curative option, however there is limited evidence to guide this approach, and outcomes are unclear [17][18][19].…”
Section: Introductionmentioning
confidence: 99%